Limites e possibilidades da inclusão escolar de deficientes no Ensino Médio modalidade Educação de (Jovens e) Adultos: percepções de alunos e professores - Silva, Reni Gomes da (2013)
The objective of this thesis is to analyze the limits and possibilities of school inclusion for students with disabilities in high school modalities EJA/Special Education. Taken as empirical field a school in the state capital of the state of São Paulo, accredited as inclusive for catering to a significant number of disabled students. As research procedures were used: bibliographic survey, documentary analysis and questionnaires answered by twelve (12) students and nine (9) teachers. The analysis of collected data was based on the theoretical contributions of Pierre Bourdieu, Escolano e Viñao Frago, Antônio Nóvoa e Licínio C. Lima. The argument is that the government agencies, federal and state policies aim to propose actions to promote school inclusion of students with disabilities or not, by means of the EJA; and school inclusion of students with disabilities, by means of the Special Education, but maintain or create a set of impediments of organizational, political, bureaucratic, such that they, rather than support, usually produce barriers to their accomplishment. At the end of the analysis, it was confirmed the hypothesis that in order to decrease the limits and extend the possibilities of achieving the proposed objectives for the EJA, eliminating the supplementary nature and focus on streamlining which nowadays characterizes this modality, besides making the inclusion of disabled students an effective educational policy through Special Education, the state would need to invest more than it has or is willing to in its "left hand" through the administrative-bureaucratic organization, financial resources and dialogue among formulators, executors and recipients of actions